2022
DOI: 10.3389/frvir.2022.889271
|View full text |Cite
|
Sign up to set email alerts
|

Head-Mounted Display-Based Virtual Reality and Physiological Computing for Stroke Rehabilitation: A Systematic Review

Abstract: Virtual reality (VR)-mediated rehabilitation is emerging as a useful tool for stroke survivors to recover motor function. Recent studies are showing that VR coupled with physiological computing (i.e., real-time measurement and analysis of different behavioral and psychophysiological signals) and feedback can lead to 1) more engaged and motivated patients, 2) reproducible treatments that can be performed at the comfort of the patient’s home, and 3) development of new proxies of intervention outcomes and success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Motor rehabilitation is a domain in which VR is actively used, as VE are under full control and allow to monitor the user precisely [39]. Additionally, cognitive-motor interference allow to use motor tasks to target cognitive rehabilitation or as a mean to create a more challenging exercise, or vice versa [40].…”
Section: B Vocational Rehabilitation Using Vr For Motor Functions Def...mentioning
confidence: 99%
See 2 more Smart Citations
“…Motor rehabilitation is a domain in which VR is actively used, as VE are under full control and allow to monitor the user precisely [39]. Additionally, cognitive-motor interference allow to use motor tasks to target cognitive rehabilitation or as a mean to create a more challenging exercise, or vice versa [40].…”
Section: B Vocational Rehabilitation Using Vr For Motor Functions Def...mentioning
confidence: 99%
“…Combined with a high sense of presence and realism, all these elements may help patients with their rehabilitation. VR applications for motor deficit combines different technological assets like exoskeletons, HMD, hand or motion tracking and haptic feedback to provide a multi-modal rehabilitation [39].…”
Section: B Vocational Rehabilitation Using Vr For Motor Functions Def...mentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual reality (VR) has emerged as one particular presentation modality that has shown to positively impact BCI performance (Vourvopoulos et al, 2016 ; Amini Gougeh and Falk, 2022a ; Arpaia et al, 2022 ; Choy et al, 2022 ). VR-based presentation can increase the sense of embodiment, improve immersion, and foster greater engagement levels, which, in turn, could lead to the generation of neural signals with increased discriminability (Škola and Liarokapis, 2018 ; Vourvopoulos et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…VR-based presentation can increase the sense of embodiment, improve immersion, and foster greater engagement levels, which, in turn, could lead to the generation of neural signals with increased discriminability (Škola and Liarokapis, 2018 ; Vourvopoulos et al, 2019 ). In fact, Amini Gougeh and Falk ( 2022a ) surveyed the literature and showed that VR coupled with MI-BCIs could lead to improved neurorehabilitation outcomes.…”
Section: Introductionmentioning
confidence: 99%